Mal Sebagai Arena Transaksi Sosial-Ekonomi dan Agen Pembentuk Budaya Konsumtif Masyarakat Urban Kota - Bambang Mudjiyanto; Launa Launa (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the position of malls as consumer arenas for urban communities. This is characterized by the phenomenon of 'Rojali-Rohana' ('rarely buying groups' and 'only asking groups'), which is perceived as a reflection of the weakening purchasing power of the urban middle class. However, urban communities demonstrate an adaptive capacity to navigate economic pressures and the absence of public spaces as arenas of contestation. Malls, which originally functioned as consumption arenas, have now transformed into multifunctional spaces: to fulfill the needs of social and emotional interaction, and to stage the battle for identity among urban communities. Through virtual phenomenological analysis, this study found an initial hypothesis: malls have become arenas where the social identity of the urban middle class is constructed, transacted, and negotiated. Malls have now positioned themselves as cultural arenas, social stages, and landscapes for changing urban lifestyles within the ever-changing urban socio-economic dynamics.